Reasons for cessation of clean intermittent catheterization after spinal cord injury: Results from the Neurogenic Bladder Research Group spinal cord injury registry. Issue 1 (2nd October 2019) - Patel, Darshan P.; Herrick, Jennifer S.; Stoffel, John T.; Elliott, Sean P.; Lenherr, Sara M.; Presson, Angela P.; Welk, Blayne; Jha, Amitabh; Myers, Jeremy B.
Abstract: Introduction: Clean intermittent catheterization (CIC) is recommended for bladder management after spinal cord injury (SCI) since it has the lowest complication rate. However, transitions from CIC to other less optimal strategies, such as indwelling catheters (IDCs) are common. In individuals with SCI who stopped CIC, we sought to determine how individual characteristics affect the bladder‐related quality of life (QoL) and the reasons for CIC cessation. Methods: The Neurogenic Bladder Research Group registry is an observational study, evaluating neurogenic bladder‐related QoL after SCI. From 1479 participants, those using IDC or urinary conduit were asked if they had ever performed CIC, for how long, and why they stopped CIC. Multivariable regression, among participants discontinuing CIC, established associations between demographics, injury characteristics, and SCI complications with bladder‐related QoL. Results: There were 176 participants who had discontinued CIC; 66 (38%) were paraplegic and 110 (63%) were male. The most common reasons for CIC cessation among all participants were inconvenience, urinary leakage, and too many urine infections. Paraplegic participants who discontinued CIC had higher mean age, better fine motor scores, and lower educational attainment and employment. Multivariable regression revealed years since SCI was associated with worse bladder symptoms (neurogenic bladder symptom score), ≥4 urinary tract infections (UTIs) in a year was associated with worse satisfaction and feelings about bladder symptoms (SCI‐QoL difficulties), while tetraplegia was associated better satisfaction and feelings about bladder symptoms (SCI‐QoL difficulties). Conclusions: Tetraplegics who have discontinued CIC have an improved QoL compared with paraplegics. SCI individuals who have discontinued CIC and have recurrent UTIs have worse QoL.